Commercially available kits for manual and automatic extraction of nucleic acids from formalin-fixed, paraffin-embedded (FFPE) tissues - Kocjan, Boštjan (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2015)
Introduction: Formalin-fixed, paraffin-embedded (FFPE) tissues represent an invaluable source for diagnostic purposes when fresh clinical material is unavailable, and also for molecular and epidemiological studies. The recovery of nucleic acids from FFPE tissues is particularly challenging, and several in-house methods have been developed for this purpose over the last three decades. Recently, several commercial kits specifically developed for DNA and/or RNA extraction from FFPE tissues have been introduced to the market, but their inventory is not available in peer-reviewed literature. Methods: This article provides the first comprehensive inventory of commercial FFPE DNA/RNA extraction kits currently available on the market and describes their basic characteristics and features. Results: A total of 69 commercial kits from 43 companies were identified. Thirty-five kits were developed specifically for DNA extraction, 22 for RNA extraction, and 12 for both DNA and RNA extraction. Only two commercial kits allow full automation of the entire nucleic acid extraction procedure. The tissue deparaffinization step is omitted in many protocols by melting paraffin directly in a tissue lysis buffer. Purification of the released nucleic acids is mainly based on silica or resin adsorption technology. A formalin reverse cross-linking step to increase the quality of extracted DNA and RNA is an intrinsic part of over half of the kits identified. Conclusions: It is hope that this comprehensive list of available commercial kits for extracting nucleic acids from FFPE will encourage researchers to strongly consider using them in diagnostic and research settings instead of old-fashioned, crude, and probably less effective in-house methods.
Keywords: commercially available kits; komercialno dostopni kompleti; nucleic acids; nukleinske kisline; tissues; tkiva